The functions and roles of C2H2 zinc finger proteins in hepatocellular carcinoma - Li, Qinguo; Tan, Guoqian; Wu, Fan (Frontiers in Physiology, 2023)
C2H2 zinc finger (C2H2-ZF) proteins are the majority group of human transcription factors and they have many different molecular functions through different combinations of zinc finger domains. One of the most prevalent malignant tumors and the main reason for cancer-related deaths worldwide is hepatocellular carcinoma (HCC). More and more findings support the abnormal expression of C2H2-ZF protein in the onset and progression of HCC. The C2H2-ZF proteins are involved in various biological functions in HCC, such as EMT, stemness maintenance, metabolic reprogramming, cell proliferation and growth, apoptosis and genomic integrity. The study of anti-tumor drug resistance also highlights the pivotal role of C2H2-ZF protein at the intersection of biological functions （EMT, stemness maintenance, autophagy）and chemoresistance in HCC. The involvement of C2H2-ZF protein found recently in regulating different molecules, signal pathways and pathophysiological activities indicates that the C2H2-ZF protein is a possible therapeutic target for the treatment in HCC and can be applied as a diagnostic or prognostic biomarker.